2013
DOI: 10.1371/journal.pone.0081506
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Correlates of Amnestic Mild Cognitive Impairment in a Simon Task

Abstract: Amnestic mild cognitive impairment (aMCI) represents a prodromal stage of Alzheimer`s disease (AD), especially when additional cognitive domains are affected (Petersen et al., 2009). Thus, single-domain amnestic MCI (sdaMCI) and multiple-domain-amnestic MCI (mdaMCI) biomarkers are important for enabling early interventions to help slow down progression of the disease. Recording event-related potentials (ERPs) is a non-invasive and inexpensive measure of brain activity associated with cognitive processes, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 79 publications
4
27
1
Order By: Relevance
“…However, the patients enrolled in the present study were in the early (mild AD) and in the prodromal phase (MCI) of the disease; therefore, a decline in the N2pc component in the later stages of the disease (i.e., moderate AD) cannot be ruled out. Contrary to the present finding, Cespon and colleagues [41,42] reported a reduction of N2pc amplitude in multi-domain amnestic MCI patients as compared to healthy elderly, suggesting the utility of N2pc to early identify a specific MCI subtype. The discrepant finding may be due to the experimental differences between the studies.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the patients enrolled in the present study were in the early (mild AD) and in the prodromal phase (MCI) of the disease; therefore, a decline in the N2pc component in the later stages of the disease (i.e., moderate AD) cannot be ruled out. Contrary to the present finding, Cespon and colleagues [41,42] reported a reduction of N2pc amplitude in multi-domain amnestic MCI patients as compared to healthy elderly, suggesting the utility of N2pc to early identify a specific MCI subtype. The discrepant finding may be due to the experimental differences between the studies.…”
Section: Discussioncontrasting
confidence: 99%
“…In a recent study, we observed altered spatial attention toward a lateralized target stimulus, as revealed by the smaller amplitude of the negativity posterior contralateral (N2pc) in mdaMCI participants than in healthy controls (Cespón et al, 2013a ). N2pc is an ERP correlate of the direction of the spatial attention to lateralized stimuli (Luck and Hillyard, 1994 ; Woodman and Luck, 1999 ; Hickey et al, 2009 ).…”
Section: Introductionmentioning
confidence: 82%
“…In those cases in which the required response is on the opposite side to the stimulus (incompatible condition), a type of interference known as the Simon effect is observed; this leads to increased reaction time (RT) and percentage of errors (PE) (for reviews, see Proctor et al, 2005 ; Leuthold, 2011 ). Several studies have shown that interference in Simon tasks increases with age of participants (van der Lubbe and Verleger, 2002 ; Proctor et al, 2005 ; Juncos-Rabadán et al, 2008 ) and it is even greater in participants with MCI (Cespón et al, 2013a ; Pereiro et al, 2014 ). However, changes in neural mechanisms underlying cognitive control processes in Simon tasks have not been studied in MCI persons.…”
Section: Introductionmentioning
confidence: 99%
“…These cognitive processes include stimulus evaluation, response execution and inhibition, conflict monitoring, planning, organizing, and decision making [10][11][12][13], all of which play a role in day-to-day activities. To characterize cognitive control and its deficits in individuals with MCI, a variety of clinical (e.g., Behavior Rating Inventory of Executive Function, the Stroop color-word task, Wisconsin Card Sorting Test, Trails B, Letter fluency) and experimental measures (e.g., the Brown-Peterson task, the Hayling task, Erickson flanker task, the Simon task, Go/NoGo task, the stop signal task) have been used [14][15][16][17][18][19][20][21][22][23][24]. Here we report on electrophysiological correlates of cognitive control involved in execution and inhibition of a response in a cohort with aMCI and a group of cognitively normal controls.…”
Section: Introductionmentioning
confidence: 99%